Brückenbauer im Kalten Krieg : Österreich und der lange Weg zur KSZE-Schlussakte - Graf-Steiner, Anna 1991- (Leykam Buchverlag, 2024)
Austria engaged in the CSCE negotiations - successfully - above all in human rights issues and humanitarian matters. Moscow's main aim with the CSCE was to consolidate the division of Europe in order to preserve its hegemony over East-Central Europe. For the first time, Soviet documents are used to show how the USSR tried to use neutral Austria to assert its interests